WATERTUBE SMOKE TUBE BOILER: NUMERICAL COMPUTER SIMULATION AND EXPERIMENT - A. V. Kanygin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2018)
The improvement of natural gas use technologies in water-heating boilers is considered. The concept of a new watertube smoke tube boiler, created on the basis of the screen radial tube bundle placement in the space of a cylindrical heat pipe-furnace. The results of numerical computer simulation of the furnace process in the 630 kW watertube smoke tube boiler are compared with the corresponding data obtained during the experiment. The analysis of the results of numerical computer simulation reveals the efficiency of the installed tube radial bundle: the total heat perception in the furnace increased by 56 %, while the growth of the part of the heat transferred by convective heat exchange occurred by 22 %; the temperature level in the furnace volume has decreased, while the concentration of nitrogen oxides has decreased by 45–51 %. It is experimentally established that the presence of the cooled screen tube radial bundle in the furnace of the watertube smoke tube boiler makes it possible: to increase heat release rate in the furnace volume by 10 %; to reduce the concentration of nitrogen oxides and carbon monoxide in flue gases by 24–40 % and 25–67 % respectively (resulting in a compliance of the level of pollutant emission to the requirements of the Ukrainian national regulations, viz. GOST 30735–2001); reduce the excess air in the furnace by 3 % and increase the efficiency of the boiler by 0.5 %. The pre-production prototype of the water-heating smoke tube boiler (KVVD-0.63 Gn) has passed the certification tests, state registration; the boiler has been adopted in permanent operation. The boiler is not complicated in manufacturing, and producible in the conditions of municipal heating network companies. The reliability of the boiler's design has been confirmed by the experience of many years of functioning.